2019
DOI: 10.1186/s40659-019-0247-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel hydrazide compound exerts anti-metastatic effect against breast cancer

Abstract: Background There are currently a number of barriers hindering the successful treatment of breast cancer, including the metastatic spread of cancer cells. In looking for new anticancer agents, we reported two novel hydrazide derivatives with anti-cancer activity in human breast cancer cells. The current study aims to explore the therapeutic potential of the most effective one, N'-((5-nitrothiophen-2-yl)methylene)-2-(phenylthio)benzohydrazide (compound B ), on metastatic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Although both docetaxel and chlorophyllin could inhibit cell migration alone, their combined treatment had a substantially stronger effect. There was no available study in literature investigating the effects of combined use of chlorophyllin with anticancer drugs on cell migration, however, these results were in line with other studies reporting that certain antioxidants and/or phytochemicals administration, such as chlorophyllin, reduced the cell migration in aggressive cancer cell lines (Lirdprapamongkol, Sakurai et al 2005, Roomi, Bhanap et al 2018, Dehghani, Kooshafar et al 2019). In a study on HT-1080 brosarcoma cells, it was shown that chlorophyllin dose-dependently reduced the cell migration, and this effect was highest at 50 µM chlorophyllin administration (Roomi, Bhanap et al 2018).…”
Section: Discussionsupporting
confidence: 67%
“…Although both docetaxel and chlorophyllin could inhibit cell migration alone, their combined treatment had a substantially stronger effect. There was no available study in literature investigating the effects of combined use of chlorophyllin with anticancer drugs on cell migration, however, these results were in line with other studies reporting that certain antioxidants and/or phytochemicals administration, such as chlorophyllin, reduced the cell migration in aggressive cancer cell lines (Lirdprapamongkol, Sakurai et al 2005, Roomi, Bhanap et al 2018, Dehghani, Kooshafar et al 2019). In a study on HT-1080 brosarcoma cells, it was shown that chlorophyllin dose-dependently reduced the cell migration, and this effect was highest at 50 µM chlorophyllin administration (Roomi, Bhanap et al 2018).…”
Section: Discussionsupporting
confidence: 67%
“…Molecular subtyping has identified three distinct histological types of breast cancer: hormone receptor (HR) positive, human epidermal growth factor receptor (HER2/neu) positive, and triple-negative (TN) (Kumar et al 2019). Triple-negative breast cancer is characterized by high invasiveness, poor prognosis and frequent relapse following treatment (Dehghani et al 2019). Triplenegative breast cancer lacks progesterone (PR), estrogen (ER) and HER2 receptor expression and the phenotype is associated with metastasis, lower survival rate and shorter life expectancy (Budzik et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among several animal models, syngeneic model is reported as the most common one to study potential of drugs against breast cancer [38]. Remarkably, this model is also a suitable model for studying the antimetastatic effect in triple-negative breast cancer [39]. Thus, it was also interesting for us to know whether this compound can modulate 4T1 cells-induced metastasis in the animals.…”
Section: Discussionmentioning
confidence: 99%